Sieving Out Relevant and Efficient Questions - De Clercq, Kristof; Verhoeven, Liza (Logique et Analyse, 2004)
Wisniewksis erotetic logic provides us with two slightly different semantic explications of the intuitive concept of a question arises from a set of declarative premises. Unfortunately, Wisniewskis erotetic concepts suffer from the drawback that they allow for the raising of irrelevant and inefficient questions. The aim of this paper is to show that raising such questions can be avoided by changing the underlying logic. Several closely related logical approaches which enable us to eliminate irrelevant and inefficient questions, are presented.